Unique Features of Mycobacterium abscessus Biofilms Formed in Synthetic Cystic Fibrosis Medium - Belardinelli, Juan M.; Li, Wei; Avanzi, Charlotte; Angala, Shiva K.; Lian, Elena; Wiersma, Crystal J.; Palčeková, Zuzana; Martin, Kevin H.; Angala, Bhanupriya; de Moura, Vinicius C. N.; Kerns, Callan; Jones, Victoria; et al. (Frontiers in Microbiology, 2021)
Characterizing Mycobacterium abscessus (MABSC) biofilms under host-relevant conditions is essential to the design of informed therapeutic strategies targeted to this persistent, drug-tolerant, population of extracellular bacilli. Using synthetic cystic fibrosis medium (SCFM) which we previously reported to closely mimic the conditions encountered by MABSC in actual cystic fibrosis (CF) sputum and a new model of biofilm formation, we show that MABSC biofilms formed under these conditions are substantially different from previously reported biofilms grown in standard laboratory media in terms of their composition, gene expression profile and stress response. Extracellular DNA, mannose-and glucose-containing glycans and phospholipids, rather than proteins and mycolic acids, were revealed as key extracellular matrix constituents holding clusters of bacilli together. None of the environmental cues previously reported to impact biofilm development had any significant effect on SCFM-grown biofilms, most likely reflecting the fact that SCFM is a nutrient-rich environment in which MABSC finds a variety of ways of coping with stresses. Finally, molecular determinants were identified that may represent attractive new targets for the development of adjunct therapeutics targeting MABSC biofilms in persons with CF.